⁠Healthcare service use for children with chronic complex diseases: a longitudinal six-year follow-up study - Pérez-Ardanaz, Bibiana; Gutiérrez-Rodríguez, Laura del Carmen; Pelaez-Cantero, María José; Morales-Asencio, José Miguel; Gómez-González, Alberto José; García-Piñero, José Miguel; Lupiáñez-Pérez, Inmaculada (Elsevier, 2024)
The objective was analysed the patterns use of healthcare services of this population and the influence of their clinical and sociodemographic characteristics.
Keywords: Niños -- Enfermedades; Enfermedades crónicas; Servicios de salud infantiles; Children; Comorbidities; Health resource; Multiple chronic conditions; Socioeconomic factors